(untitled) (Bangladesh Journal of Infectious Diseases, 2021)
Background: Detection of acute kidney injury is very essential among the children. Objective: The purpose of the present study was to validate the serum cystatin C for the detection of acute kidney injury in children. Methodology: This cross-sectional study was conducted in the Department of Paediatric Nephrology with the collaboration of Paediatric Gastroenterology, Paediatric Neurology, Paediatric Neonatology and Microbiology and Immunology at Bangabandhu Sheikh Mujib University, Dhaka, Bangladesh from May 2018 to July 2019 for a period of one year. Patients with the age group of 1 month to 17 years, who were at risk of AKI, and admitted in the inpatient department of Pediatrics and allied at Bangabandhu Sheikh Mujib University, Dhaka, Bangladesh during this study period in both sexes were selected as study population. To detect AKI, serum creatinine was measured at 0 h (baseline), 48 h and 5th day respectively. Serum cystatin C were measured at 0 (baseline) and 48 h respectively for all patients. Result: A total number of 52 patients were enrolled in this study. Here the AUC was 0.93 with 95% CI (0.864 - 0.995). Serum cystatin C had sensitivity of 95% (95% CI 77.9%-099.7%) with specificity 84% (95% CI 73.7%-87.3%), PPV 79% (95% CI 64.9%-83.1%), NPV 96% (95% CI 84.2%-99.8%), accuracy 88.7% (95% CI 75.3%-92.1%), positive likelihood ratio 6.08 and negative likelihood ratio 0.06 (95% CI 2.96-7.87 and 0.003-0.300 respectively). Conclusion: In conclusion the diagnostic validity of serum cystatin C for the detection of AKI is very high among the children. Bangladesh Journal of Infectious Diseases 2020;7(2):44-48